Relasi Suami Istri dalam Pengelolaan Keuangan Keluarga Sebagai Indikator Terjadinya Nusyuz Perspektif Hukum Islam (Studi Pemikiran Burhanuddin Ibrahim al-Bajuri bin Syaikh Muhammad al-Jizawi bin Ahmad) - Muzakkir. S (STIS DAFA MATARAM, 2024)
This research aims to investigate how the relationship between husband and wife in managing family finances can serve as an indicator of nusyuz, considering the perspectives of Islamic law and economics as articulated by Burhanuddin Ibrahim al-Bajuri from the intellectual legacy of Sheikh Muhammad al-Jizawi bin Ahmad. Family financial management is not only about practical aspects but also reflects the moral and ethical values governed by Islamic law. The methodology used is a qualitative research type with a phenomenological approach and a study of thought. The findings from this research are expected to provide deep insights into how these principles can be applied to strengthen the relationship between husband and wife and prevent domestic conflicts. This research is expected to provide ideas that strengthen the concept of good relationships according to Islamic teachings.